Når ChatGPT tager ordet: En analyse af afsenderrollen i e-mailkommunikation - Hallenslev Larsen, Melissa (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2024)
This paper investigates the impact of ChatGPT on the sender’s role in digital communication, specifically focusing on email correspondence. By conducting semi-structured interviews with three participants, the research examines their experiences in using ChatGPT to draft emails. The study applies Erving Goffman’s theories of Footing and Framing to analyze shifts in the participants’ self-perception as senders when assisted by AI. The findings indicate that while participants initially perceive ChatGPT as a mere tool, they gradually recognize its significant influence on the final product, leading to a sense of detachment from the email. This detachment arises because the generated language does not align with their personal voice. Despite this, participants remain ambivalent about ChatGPT’s role, fluctuating between viewing it as a helpful tool and acknowledging its deeper involvement. The study concludes that, although ChatGPT does not directly alter the participants’ core viewpoints, prolonged use may subtly influence their communication style over time, potentially making their expression feel less personal.